ANALISIS PENERAPAN KNOWLEDGE MANAGEMENT PADA PT TELKOM INDONESIA (PERSERO) DIVRE IV SEMARANG - Maulida Nailis Sa'adah; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2017)
Knowledge management is one of the strategies applied by PT. Telkom Indonesia Divre IV Human Resources unit to compete in global era. Management PT. Telkom Indonesia hopes through the knowledge management implementation will increase innovation and will indirectly improve the performance of PT. Telkom Indonesia Divre IV HR unit. Knowledge management include  three components namely personal knowledge, job procedures, and technology. The research purpose  to find out how the knowledge management application on employee performance at PT. Telkom Indonesia Divre IV.This research type is qualitative research with data collection technique through interview. This key informant selection technique uses purposive sampling technique. This research uses qualitative analysis technique. The research method used is analytical descriptive approach. The results showed that personal knowledge, job procedures, and technology management effort is good. Based on the training has been running, the company prioritizes the provision of training to employees who deal directly with consumers. Knowledge sharing constraints is reading culture is still lacking, it would be better if reading culture is improved, as well as get special monitoring from the company.